A leading role for the EU in drafting criminal law powers? Use of the Council of Europe for policy laundering. Issue 2 (June 2019) - De Hert, Paul; Aguinaldo, Angela
In light of the ongoing story on the regulatory steps towards electronic evidence and transnational production orders, civil rights organizations have expressed both alarm and astonishment on the regulatory initiatives in the Council of Europe regarding transnational production orders. Member states of the European Union (EU) engage actively in soft law entrepreneurship by allowing themselves to obtain directly from service providers subscriber and other communications content. This has not only been done domestically through national laws but likewise on a multilateral level as EU member states are now seen drawn towards the Council of Europe. Within said Council of Europe, member states are now enabled to stretch the extraterritorial powers exercised by their law enforcement authorities in obtaining electronic evidence through a controversial Guidance Note and soon, a Second Additional Protocol. Interestingly, throughout these developments, the EU remained passive but as of late, has come up with proposals for the European Production and Preservation Orders, among others. The mixture of alarm and astonishment among civil liberties representatives about the decision making procedures at the level of the Council of Europe can be best understood in a broader regulatory context of policy enterpreneurship, rent-seeking behaviour and, overall, rational choice institutionalism. Comparing the Council of Europe with the EU, the structure of the former makes it the more attractive venue for policy actors such as law enforcement authorities to maximize their benefits at the least amount of costs. Being competitors in policymaking vis-à-vis cooperation in criminal matters, the EU can however lose its sociopolitical ascendancy over time as an institutional venue to discuss cooperation matters. In light of this, one should not forget that two Europes coexist. These coexisting realities are now being used to the advantage of laundering policies, testing which forum would maximize benefits the most. These developments should caution us that there might be a systemic failure in ensuring safeguards in criminal investigations are always in place.